Revision of the black fungus gnat species (Diptera: Sciaridae) described by W.A. Steffan from Micronesia - Broadley, Adam; Kauschke, Ellen; Mohrig, Werner (Zootaxa, 2019)
On the Micronesian Islands 20 species belonging to ten sciarid genera were detected. The revision resulted in the following three new combinations: Cratyna brevipalpis (Steffan) comb. n., Epidapus jaluitensis (Steffan) comb. n., and Epidapus yapensis (Steffan) comb. n. Two species are declared as new synonyms: B. snyderi Steffan, 1969 syn. n. of Bradysia kraussi Steffan, 1969 and Epidapus nanus Menzel, 2007 syn. n. of Epidapus jaluitensis (Steffan, 1969). Bradysia radicum (Brunetti, 1912) was misinterpreted by Steffan and is not yet known to occur in Micronesia. All revised species are figured.